Company Value Moderates The Relationship Of Profitability, Liquidity, And Political Connections To Stock Returns - Rahmawati Sugito, Alfina; Purnamasari, Puji Endah (Politeknik Piksi Ganesha Indonesia, 2024)
TInvestors increasingly demand stock investments, as evidenced by the number of Indonesian capital market investors reaching 10 million in 2022. This surge shows the public's high interest in gaining profits from stock investments, necessitating in-depth research on factors influencing stock returns for optimal profits. This research examines the influence of profitability, liquidity, and political connections on stock returns, using firm value as a moderating variable. Employing a quantitative, descriptive methodology and purposive sampling, 29 firms listed in LQ45 from 2020-2022 were selected. The study uses primary and secondary data, analyzed with Eviews 12 software through a panel data regression model. Findings reveal that profitability positively affects stock returns, while liquidity and political connections do not. However, firm value affects stock returns and can moderate the impact of profitability but not liquidity or political connections.